Intersection of two surfaces in GeoGebra - Dos Santos, José Manuel Dos Santos (Revista do Instituto GeoGebra Internacional de São Paulo, 2017)
In this article our main objective is to illustrate how GeoGebra can be used to obtain the intersection of some surfaces of R3, presenting several examples, and the procedures necessary to its construction. The intersection of the surfaces associated with the graph representations of bivariate functions is show in more detail. Some of the constraints of the application of these processes are presented, as well as their relation with some topics of algebraic geometry. Finally, some considerations are presented in the educational context where the material here presented can be used with students of mathematics courses in higher education.